2015
DOI: 10.4103/0970-9185.161679
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and pharmacologic aspects of peripheral nerve blocks

Abstract: A successful peripheral nerve block not only involves a proper technique, but also a thorough knowledge and understanding of the physiology of nerve conduction and pharmacology of local anesthetics (LAs). This article focuses on what happens after the block. Pharmacodynamics of LAs, underlying mechanisms of clinically observable phenomena such as differential blockade, tachyphylaxis, C fiber resistance, tonic and phasic blockade and effect of volume and concentration of LAs. Judicious use of additives along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 78 publications
1
26
0
1
Order By: Relevance
“…Thereby, the patients were randomly divided into two groups; the first Group (M) received 4 mg/kg lidocaine 1% (Aburaihan Co., Iran) plus 50 micg fentanyl plus 5 mL magnesium sulfate 20% (Pasteur Institute, Iran), and the second group (N) received 4 mg/kg lidocaine 1% plus 50 micg fentanyl plus 5 mL normal saline 0.9%. The dose of magnesium sulfate was determined based on previous studies ( 1 , 12 ). The nurse of operation room prepared the drug components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, the patients were randomly divided into two groups; the first Group (M) received 4 mg/kg lidocaine 1% (Aburaihan Co., Iran) plus 50 micg fentanyl plus 5 mL magnesium sulfate 20% (Pasteur Institute, Iran), and the second group (N) received 4 mg/kg lidocaine 1% plus 50 micg fentanyl plus 5 mL normal saline 0.9%. The dose of magnesium sulfate was determined based on previous studies ( 1 , 12 ). The nurse of operation room prepared the drug components.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, it has been shown that magnesium sulfate decreased the effects of aminoamide local anesthetics on rat sciatic nerves in vivo. Hence, based on this paradoxical data, currently magnesium cannot be recommended as an adjuvant to enhance nerve blocks and needs to further studies ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zahvaljujući upotrebi ultrazvuka, kojim je omogućena vizuelizacija ne samo nervnih struktura nego i mesta davanja lokalnog anestetika, danas su definisane tri tehnike: intraneuralna, intrapleksus i peripleksus, i uveden je pojam minimalnog efektivnog volumena (MEV) i minimalne efektivne anestetičke koncentracije (MEAC). Pokazano je da je minimalni volumen za blokadu brahijanog pleksusa oko 32 ml, nezavisno od tehnike koja se koristi 64 . Ali pod kontrolom ultrazvuka blok je uspešan i samo sa 2 ml po nervu, kada je u pitanju mekotkivna hirurgija 65 .…”
Section: Diskusijaunclassified
“…In alkaline conditions, local anesthetics are predominantly uncharged which maximizes their permeability through the cellular lipid bilayer. Existence in an uncharged and highly permeable form is essential to the function of local anesthetics because they must bind to the cytoplasmic side of Nav channels [64]. Accordingly, local anesthetics are not generally used as an analgesic in conditions of acidic or inflammatory pain (e.g., rheumatoid arthritis) because protonation results in ionization, decreased permeability, and poor efficacy.…”
Section: Voltage-gated Sodium Channel Pharmacologymentioning
confidence: 99%